2016
DOI: 10.1007/s00595-016-1316-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intermittent portal clamping on the early recurrence of hepatocellular carcinoma after surgery

Abstract: IPC is an independent risk factor for the early recurrence of HCC after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…OS and DFS are reported to be irrelevant with IPM for colorectal liver metastasis [33,34], but it has yet to be known for HCC. In this study, six studies [21,22,27,28,29,30] were eligible for this metaanalysis, including the latest report from the western series [22]. Resulted showed that longterm outcomes were comparable between groups of IPM and non-IPM, which was in line with the most of the eastern series and the newly-published western series.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…OS and DFS are reported to be irrelevant with IPM for colorectal liver metastasis [33,34], but it has yet to be known for HCC. In this study, six studies [21,22,27,28,29,30] were eligible for this metaanalysis, including the latest report from the western series [22]. Resulted showed that longterm outcomes were comparable between groups of IPM and non-IPM, which was in line with the most of the eastern series and the newly-published western series.…”
Section: Discussionsupporting
confidence: 53%
“…After browsing titles and abstracts, 439 records were excluded, including 38 were for lack of comparison, 66 were for benign disease, 20 were for data unavailable, 66 were for palliative treatment, 168 were for not specified for HCC, 45 were for in vitro studies, 36 were for reviews. Among the remained 109 records, 103 records were excluded for comparison PM with selective PM, Finally, six researches [21,22,27,28,29,30] were included for analysis. Details were depicted specifically in Fig 1. In total, 5275 patients were enrolled in this meta-analysis, with 3290 cases in the IPM group and 1985 cases in the non-IPM group.…”
Section: Base Characteristic Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations